WORK ENGAGEMENT AND JOB SATISFACTION AMONG HEALTHCARE PERSONNEL IN BAJA CALIFORNIA, MEXICO: Psicologia Organizacional - Contreras-Preciado, Marco Alfonso; Nava-Gómez, Martha Eugenia; Brito-Ortiz, José Félix; Cruz-Gonzalez, Anzony Arturo; Contreras, Hugo Isaac Plascencia (Veredas do Direito, 2026)
Introduction: Among the antecedents of job satisfaction, work engagement stands out. Work engagement is considered a form of work-related happiness. Objective: To test a structural model representing the hypothetical relationships between work engagement and job satisfaction in a sample of nursing professionals completing their social service in northern Mexico. Methods: A cross-sectional study using self-administered questionnaires was conducted. The sample consisted of 71 nursing professionals from five hospitals in northern Mexico, with a 100% response rate. Results: Work engagement was positively and significantly associated with job satisfaction. Structural equation modeling indicated that engagement is a significant predictor of participants’ job satisfaction. Conclusions: Interventions aimed at improving quality of work life help maintain high levels of engagement and job satisfaction among nursing professionals performing social service.